Automated systems in the aviation and aerospace industries - Shmelova, Tetiana, 1961-; Sikirda, Yuliya, 1978-; Rizun, Nina, 1968-; Kucherov, Dmytro; Dergachov, Konstantin (IGI Global, Engineering Science Reference, an imprint of IGI Global, 2019)
"This book explores the use of automated systems in the aviation and aerospace industries. It also examines the challenges and issues surrounding the development of training for automated systems"-- Provided by publisher
Keywords: Aeronautics -- Technological innovations.; Aerospace industries -- Automation.; Automatic pilot (Airplanes); Aeronautics -- Study and teaching -- Data processing.; elektronické knihy; electronic books